PERAN KANTOR PERTANAHAN DALAM UPAYA MENINGKATKAN JAMINAN KEPASTIAN HUKUM HAK ATAS TANAH MELALUI PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KABUPATEN KARANGANYAR - SUHENDRO, JOKO (Dinamika Hukum, 2019)
Role of the Land Office in the Complete Implementation of Systematic Land Registration: responsible for the implementation of Complete Systematic Land Registration, establishing and stipulating the composition of the Acceleration Adjudication Committee and PTSL Juridical Task Force, reporting the implementation of Complete Systematic Land Registration to the Head of Regional Office of the National Land Agency, signing the News File reception program and documentary results of Systematic Land Registration Complete from the Acceleration Adjudication Committee to be kept as an archive, ensuring the completeness of the application documents so that they formally fulfill the requirements for processing and issuing certificates of land rights as proof of strong ownership of land rights and guaranteeing legal rights on the land and the physical task force ensures that the land object is correct, clearly demarcated and has been installed by the owner. The obstacles faced and efforts made in the implementation of Complete Systematic Land Registration (PTSL) and efforts to improve the Certainty of Land Rights Law Certainty in Karanganyar Regency are as follows: 1) Lack of public knowledge of the importance of data collection, 2) Location of rights objects in SPPT blocks is not in accordance with the pictures of the United Nations block map, 3) Human Resources Facilities and Infrastructure, and 4) Costs that are borne by the Applicant or the Community. Keywords: Role, Legal Certainty Guarantee, Land Rights, Complete Systematic Land Registration